Trust in the Sharing Economy - Katarzyna Czernek (Gospodarka Narodowa. The Polish Journal of Economics, 2018)
The so-called sharing economy is one of the most important and widespread manifestations of technological progress, reflecting the growth of the “new economy.” It can be understood as a socio-economic model based on the grassroots initiatives of individual people (P2P relationships) that refer to not fully utilised resources, with sharing taking place through technology platforms, for a fee or free of charge. The aim of this article is a detailed description of trust, which is a foundation and an inalienable element of the sharing economy. The definitions and features of the sharing economy are presented, followed by the concept and functions as well as selected mechanisms of trust building. Subsequently, the concept of the so-called inter-intermediary trust, characteristic of the sharing economy, is introduced and outlined, and the mechanisms of its creation are described. Next, we discuss differences between trust and credibility and problems with building the credibility of digital platform users. The study finds that intermediary trust is inseparably connected with the sharing economy.